Faktor–Faktor Rasio Keuangan Yang Mempengaruhi Non-Performing Loan (NPL) - Widya Hasnadz Dzakiyani; Hermanto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research was conducted with the aim of examining the factors that influence Non-Performing Loan (NPL), such as Return on Assets (ROA), Capital Adequacy Ratio (CAR), Bank efficiency, Diversification Income, Current Account Saving Account (CASA). The population in this research is from the banking subsector listed on the IDX during the period 2018 to 2022, using data from the annual financial statements of conventional banks. The data collection technique in this research uses the Purposive sampling method using secondary data, so that 75 data from 25 companies in the banking subsector in Indonesia are obtained. This research is processed by multiple linear regression analysis using JASP statistical data processing application. The research results can be interpreted that return on assets (ROA) has a negative but insignificant effect on NPL. Capital Adequacy Ratio (CAR), Diversification Income and Current Account Saving Account (CASA) have a negative and significant effect on NPL. Meanwhile, bank efficiency has a positive and significant effect on NPL.